Coffee house consumer behavior in Changsha, China - Hoefener, Karen (2015)
Women in Changsha are patronizing coffee-houses, ordering beverages and sweets, and disliking the taste of the expensive product purchased. This thesis is an exploratory research study conducted in Changsha, China with a consumer behavior focus. It uses primary surveys and interviews in addition to secondary sources from books, articles, and academic journals. It seeks to identify underlying motives for purchasing behavior from working women in the developing third-tier city Changsha, Hunan, China. It delves into the psychology of the working women who spend their hard-earned discretionary incomes at costly western chain coffee-houses. The inland mass-market consumer class feels the desire to project their newly established status while needing to save money for their personal future, their children’s schooling, and their parent’s retirement. They must wisely spend discretionary income while satisfying social societal norms. An individual’s self-concept plays and important role in determining which coffee shop she will frequent and what she will order. Daylight Donuts, Starbucks, Costa Coffee and local café’s all serve brewed coffee but they have different associations. This study aims at understanding the influencing factors associated with coffee-house brand equity and how the consumer’s perception of the brand forms her purchasing behavior. All coffee-house brands are relatively new in Changsha, none existing more than seven years. They do not have lasting ties with the community and need to create consumer relationships to ensure sustainability. Changsha women are bold and strong willed. If a corporation is to succeed in the future of Hunan, it will need to create an environment of hospitality excellence, place socially responsible roots in the society, and ask its customers what they want.